ANALISIS PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN (PSAP) PADA PUSAT KESEHATAN MASYARAKAT CIBUGEL KABUPATEN SUMEDANG - Salamatul Afiyah; Annida Aljannatul Arsy; Engkus Engkus (Jurnal Inovasi Penelitian, 2021)
This research is motivated by the principles of transparent and accountable financial management so that it is a description of the transactions that occur from the use of economic resources in one period. The problem of this research is that the presentation of the financial statements of the Cibugel Community Health Center (Puskesmas) in Sumedang Regency in 2018 - 2020 is less than optimal. In 2018 the percentage was only 78%. The purpose of this study was to determine how the implementation, obstacles, and efforts in the presentation of financial statements based on PSAP. The research method used is a qualitative research method with a descriptive approach. The data sources used are primary and secondary data sources related to the analysis of the application of PSAP Number 13 in the Cibugel Health Center Financial Report. Data collection techniques used are observation, interviews, and documentation studies. The results of the research have shown that the application of PSAP Number 13 to the Financial Statements of the Cibugel Health Center, Sumedang Regency has been implemented, but not fully because there are still several components of the financial statements that are not in accordance with the rules contained in PSAP Number 13.